2021
DOI: 10.31458/iejes.895103
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the Relationship between Competencies of Candidate Teachers in Classroom Management and Teacher Efficacy

Abstract: The aim of this study is to examine the relationship between competencies of candidate teachers in classroom management and teacher efficacy. This descriptive research is in correlational survey model. The study group consists of a total of 368 students studying in the pedagogical formation program at Aydın Adnan Menderes University. In order to collect the data, Competencies of Candidate Teachers in Classroom Management Scale and Ohio Teacher Efficacy Scale were used. Normality tests, correlation coefficient,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
1
1
0
Order By: Relevance
“…They reported that academic procrastination among learners correlated positively and moderately with their AtC. The similarity between the finding of the present study conducted in an L2 context and that of a study by Saracaloğlu et al (2021) conducted outside the L2 context may give an early picture of the direction of interaction between academic procrastination and AtC. Intuitively speaking, procrastinating learners may find themselves with limited time left to complete tasks because they delay working on the tasks until much later.…”
Section: The Relationship Between Learners' Procrastination and Their...supporting
confidence: 74%
See 1 more Smart Citation
“…They reported that academic procrastination among learners correlated positively and moderately with their AtC. The similarity between the finding of the present study conducted in an L2 context and that of a study by Saracaloğlu et al (2021) conducted outside the L2 context may give an early picture of the direction of interaction between academic procrastination and AtC. Intuitively speaking, procrastinating learners may find themselves with limited time left to complete tasks because they delay working on the tasks until much later.…”
Section: The Relationship Between Learners' Procrastination and Their...supporting
confidence: 74%
“…However, their study eventually reported that there was no association between learners' academic procrastination with academic dishonesty. In comparison, a study in Iran by Saracaloğlu et al (2021) reported that academic procrastination among graduate and undergraduate learners correlated positively and moderately with their attitude toward cheating. Thus, the relationship between procrastination and cheating has not been firmly established.…”
Section: Cheating and Absenteeism: Potential Interactions With Academ...mentioning
confidence: 84%